Moiré Fringe Phase Difference Measurement Based on Spectrum Zoom Technology - Li Chang; Gai Cui (Institute of Advanced Engineering and Science, 2013)
Grating displacement measurement technique is an important means to achieve precise displacement measurement of nanometer scale. Moiré fringe phase difference measurement is the basis of grating displacement measurement technique. Traditional Moiré fringe subdivision method based on DFT algorithm has low frequency resolution relatively when extracting Moiré fringe fundamental frequency spectral line, which causes frequency and phase measurement errors of Moiré fringe fundamental frequency. CZT spectrum zoom technique can improve the frequency resolution of frequency band near Moiré fringe fundamental frequency and get fundamental frequency spectrum lines more exactly, which can solve the problem of low frequency resolution of DFT. The paper studies the relation of Moiré fringe phase difference and grating displacement, and analyzes the working principles of DFT and CZT spectrum zoom method. DFT and CZT spectrum zoom are used for Moiré fringe spectrum analysis and phase difference calculation respectively. Simulation results show measurement error of Moiré fringe phase difference with DFT algorithm is in 10-3degree scale, while measurement error with CZT spectrum zoom algorithm is approximate 0 degree. The comparison results show CZT spectrum zoom method has better performance and applicability, which improves the phase difference measurement accuracy of Moiré fringe effectively. DOI: http://dx.doi.org/10.11591/telkomnika.v11i10.3461